The potential of exogenous specialized pro-resolving mediators in protecting against sepsis-associated lung injury: a review - Shen, Jiwei; Shen, Huiqin; Sun, Shujun; Fan, Shiwen; Zhang, Tianhao; Song, Guobin; An, Ning; Chen, Xiangdong; Gao, Yafen (Frontiers in Pharmacology, 2025)
Sepsis-associated lung injury (SALI) is a critical condition with high mortality. Current therapies are limited, necessitating novel approaches. This review highlights the potential of exogenous Specialized Pro-resolving Mediators (SPMs), including lipoxins, resolvins, protectins, and maresins, in mitigating SALI. SPMs, derived from polyunsaturated fatty acids, exert protective effects through multiple mechanisms: enhancing alveolar fluid clearance by upregulating ENaC, Na,K-ATPase, CFTR, and AQP5; reducing alveolar epithelial cell apoptosis and epithelial-mesenchymal transition; preserving endothelial glycocalyx integrity via modulating heparanase and exostosin-1 expression; alleviating oxidative stress and mitochondrial dysfunction by scavenging ROS and activating Nrf2; and immunomodulation by limiting neutrophil infiltration, promoting macrophage efferocytosis and M2 polarization, and dampening pro-inflammatory cytokine production. Notably, SPMs like RvD2 remain effective even during sepsis’ immunosuppressive phase. While significant debates persist regarding endogenous SPM generation, receptor mechanisms, and critically the reliable detection and physiological relevance of specific SPMs in biological samples like lung tissue (with earlier reports often misidentifying analytical artifacts or failing LOD/LOQ validation), recent evidence suggests exogenous SPMs act via biased allosteric modulation of the EP4 receptor to stimulate phagocytosis and resolution. Extensive preclinical evidence underscores SPMs’ promise in restoring immune homeostasis in SALI, though pharmacokinetic limitations of high-dose exogenous administration require consideration. Future high-quality clinical trials are essential to translate this resolution pharmacology approach into clinical practice.